Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1074/jbc.m113.486076
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Polyglutamine-containing N-terminal Huntingtin Fragments Are Entirely Degraded by Mammalian Proteasomes

Abstract: Background: Huntington disease is caused by an expanded polyglutamine repeat within the protein huntingtin. Results: Proteasomal degradation of mutant huntingtin fragments is devoid of polyglutamine peptides as partial cleavage products. Conclusion: Mammalian proteasomes are capable of entirely degrading expanded polyglutamine sequences. Significance: Accelerating the mutant huntingtin degradation by the proteasomal pathway obviates toxic species and represents a beneficial therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 82 publications
2
55
1
1
Order By: Relevance
“…Moreover, mutant huntingtin fragments have not been found to inhibit degradation of ubiquitylated substrates by the 26S proteasome in vitro (Hipp et al, 2012). Whether or not polyQ proteins can be degraded by the mammalian proteasome has been the subject of a considerable debate (Venkatraman et al, 2004; Pratt and Rechsteiner, 2008; Juenemann et al, 2013). Puromycin-sensitive aminopeptidase has been identified as the main cytosolic protease to efficiently clear expanded polyQ peptides generated by the proteasome in vitro (Bhutani et al, 2007).…”
Section: Proteasome Activity In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mutant huntingtin fragments have not been found to inhibit degradation of ubiquitylated substrates by the 26S proteasome in vitro (Hipp et al, 2012). Whether or not polyQ proteins can be degraded by the mammalian proteasome has been the subject of a considerable debate (Venkatraman et al, 2004; Pratt and Rechsteiner, 2008; Juenemann et al, 2013). Puromycin-sensitive aminopeptidase has been identified as the main cytosolic protease to efficiently clear expanded polyQ peptides generated by the proteasome in vitro (Bhutani et al, 2007).…”
Section: Proteasome Activity In Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, the question remains whether or not the proteasome can efficiently degrade disease-linked proteins. Some studies have suggested that the proteasome cannot degrade the polyQ proteins (Dyer and McMurray, 2001; Jana et al, 2001; Holmberg et al, 2004; Venkatraman et al, 2004) whereas others other reports show that they can be efficiently degraded by the proteasome as long as they remain in a soluble state (Verhoef et al, 2002; Kaytor et al, 2004; Michalik and Van Broeckhoven, 2004; Juenemann et al, 2013; Tsvetkov et al, 2013). Also, α-synuclein, expression levels of which can predispose individuals to PD (Singleton et al, 2003), can be degraded by the proteasome (Bennett et al, 1999), suggesting that other aggregation-prone proteins can be targeted by the UPS.…”
Section: Reducing Levels Of Neurodegeneration-associated Proteinsmentioning
confidence: 99%
“…Filter Trap Assay-The filter trap assay was carried out essentially as described by Juenemann et al (28). Briefly, the pellet fraction of the cell lysate was suspended in the benzonase buffer (1 mM MgCl 2 , 50 mM Tris/HCl, pH 8.0) and treated with an RNase/DNase mixture (50 units each; Fermentas) and incubated for 1 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Although it appears unlikely that a fully intact aggresome can be enveloped into a single autophagosome, smaller aggregated structures up to 1 μm in diameter have been found within these double-membraned structures (Filimonenko et al, 2010). Earlier structures that contribute to aggregate formation, such as misfolded monomeric or perhaps early oligomeric states of an aggregating proteins, might also depend on other degradative pathways, such as the proteasome or chaperone-mediated autophagy (Mak et al, 2010;Ortega and Lucas, 2014;Juenemann et al, 2013;Schipper-Krom et al, 2014;Thompson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%